Dorośli (i dorosłość) w pismach Janusza Korczaka - Maria Szczepska-Pustkowska (Problemy Wczesnej Edukacji)
Analyzing the texts of Janusz Korczak, we focus mainly on the child (and childhood), which he put in the center of his reflections. He emphasized the importance of childhood humanity (full and not maimed), associated with it: the dignity of the child and respect for him and the world he created. The purpose of this text is to reflect on how Korczak perceived adults and adulthood and what meaning he gave them in his writings. In order to achieve such a goal, a phenomenographic analysis of the content of several leading works of Janusz Korczak was made. It seems that this topic, although not as expressive in his works as the theme of a child and childhood, is equally important, because in the care and education for centuries, children and adults face each other.